If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1 + x + x = 6.4 Reorder the terms: -1 + 3x + x + x = 6.4 Combine like terms: 3x + x = 4x -1 + 4x + x = 6.4 Combine like terms: 4x + x = 5x -1 + 5x = 6.4 Solving -1 + 5x = 6.4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5x = 6.4 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = 6.4 + 1 5x = 6.4 + 1 Combine like terms: 6.4 + 1 = 7.4 5x = 7.4 Divide each side by '5'. x = 1.48 Simplifying x = 1.48
| 3(2x-6)=-4(x-2) | | c^2=33 | | -z-3.2=-22.8+3z | | 0.05(342-x)+0.07x=72 | | 2x+2(x-1)=2x-16+3x | | 3(2x-4)=-4(x-2) | | 16x^2=144-9y^2 | | (10m)/(5m) | | 4x=-2(3x-5) | | z^3-3iz^2-3z+i+1=0 | | 10m/5m | | -9x+12x-10-4x-2x=47 | | 0.3x+0.4=0.9x-1.4 | | 3x^2-8k=16 | | 2y-10x^2+4=0 | | 8+3m-3=9m+12-5m | | 4t-6=12t-24+18 | | 78+3x=10x-97 | | 6/z-3/z=15 | | 2(2x-3)=4(2x+2) | | 12-x/2=x/5 | | 2x-5/12-3x/6=11/12 | | 4x^2-2x+30=0 | | 5x+35=86 | | 13=3(x-4)-(x-9) | | 76+6x=-11x-145 | | G(x)=2x+1 | | 0.5x+1.9=0.8x-0.2 | | (4x-9z)(3x+5z)= | | 7x-20=33 | | (x^6y^-3/z^-1)-5 | | 0.19x+0.2(x-4)=0.01(5x-2) |